Performance evaluation of potential drought tolerant hybrid clones of rubber in a dry sub-humid region. - Abraham, T.; Sathik, M.B.M.; Ravichandran, S.; Mydin, K.K.; Singh, M. (Rubber Science, 37(1): 2024. 50-53.)
Somatic embryogenesis (SE) is an illustration of cellular totipotency, given that a single plant cell can regenerate into a complete and functional plant. Unlike organogenesis, SE is the most important in vitro pathway, having wide applications both in basic and applied research. Among various stages, the developmental transition from somatic cell to embryogenic cell is the key step in SE. This transitional reprogramming is influenced by various external and internal factors. Although substantial progress has been made in understanding these factors for many plant species, the molecular mechanisms behind SE remain largely unknown. This review provides information on various factors influencing SE. Moreover, a few embryogenesis specific genes, gene encoded proteins and enzymes and other stress factors recently identified have been discussed briefly. An overview of current progress made in woody plants SE mainly on potential genes is also highlighted. Research developments on SE in rubber with a focus on molecular innovations are also summarized.
Keywords: Clonal nursery evaluation; Drought tolerance; Hybrids